(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Natural fragrant microcapsules with ethyl cellulose (EC) as a shell and lavender oil as a core were prepared by emulsify-solvent diffusion method. The characters, including particle size, encapsulation efficiency and oil loading capacity, were tested and analyzed by using orthogonal design. The processing parameters of the ratio of an oil phase to water phase, the ratio of core material to shell material, concentration of PVA and stirring speed were evaluated. The morphology and structure features of microcapsules were studied by SEM, FT-IR and etc. The results showed that the microcapsules were in sphere shape and most of the particle size was about 1